A expansão da educação superior e o trabalho docente no Instituto Federal do Norte de Minas Gerais - Paula Francisca da Silva (2015)
This paper aimed to analyze the reorganization process in the Federal Network of Technological Education (REFT) in the context of expansion of higher education (HE) and its repercussions on professor's work in higher education, taking as a field of study the Federal Institute in the North of Minas Gerais (FINMG). The research issue was guided in order to identify what was interfering with the exercise of teaching in the higher education of FINMG in the context of amendments set by the HE expansion policy. The qualitative research included desk research, observation and interviews as data collection instruments. The study showed that the offering of HE in the middle of the professional and technological education reforms was consolidated in the REFT with the Federal Institutes (FI) which now act as the HE blowing agents. In FINMG this expansion occurs in accelerated procedure with regard to the increased supply of higher education, but slows in adapting to the institution regulations and norms, the implementation of the necessary infrastructure and recruitment of teachers in sufficient numbers. The institution model followed by implanted FINMG is marked by the multi-campus organization that optimizes space, infrastructure, human and material resources at a lower cost; offer becomes more flexible and diversified courses as far as the level and the type of education; numerous goals to accomplish; and by the intimate relationship of the institute with the market. The way the institution expansion and its courses occur, set the professors to precarious working conditions, since the professors are not given all the necessary conditions. However, requires a multifunctional profile of teachers in order to develop multiple activities and cover the institutional gaps. In general, the professors realized the changes that happened in FINMG and encountered difficulties imposed by the expansion and achievement of goals. It might be inferred that the nature and complexity of education offered in the FI, in general, put the professors underworked intensification and the lack of minimum working conditions is a recurring demand of teachers, including the agendas of their union claims.